Clinical characteristics and management of post-myocardial infarction patients with stable angina in the outpatient practice of Ukrainian cardiologists (GO-OD study) - O. M. Parkhomenko; M. Yu. Kolesnyk; O. A. Koval; S. A. Tykhonova (Zaporožskij Medicinskij Žurnal)
Aim. To identify the clinical and anamnestic characteristics and features of the stable angina management in patients with a history of myocardial infarction (MI) in the actual outpatient practice of Ukrainian cardiologists in order to determine the follow-up activities for optimizing and individualizing the treatment of this patient cohort.